The Influence of the World Economic Crisis on the Pension Funds in Bulgaria (UNWE Yearbook, 2009)
This paper aims to show how the World financial crisis affected the institutions for additional pension insurance in Bulgaria. The Bulgarian economy is small and open so that it was not possible to stay isolated by the crisis which escalated in Europe and the whole World. The recession of the Bulgarian economy was predetermined by its dependency from the foreign investments and the European export market. The sharp decline of the financial asset prices, the rise of the interest rates and the financial difficulties of many enterprises had a negative impact on the Bulgarian pension funds. The long – term investment horizon of the pension funds from the second pillar will give them an opportunity to recover their losses. The voluntary pension funds from the third pillar, however, realized losses which will be hard to recoup in the next few years when some people are going to retire. Risk management measures will play more and more important role for the institutions for additional pension insurance in Bulgaria. Careful financial instrument selection and diversification will be crucial in the following years.